Assessment of serum catalase, reduced glutathione, and superoxide dismutase activities and malondialdehyde levels in keratoconus patients - Tekin, Serek; Seven, Erbil (Eye (London), 2022)
Background The aim of this study was to investigate the relationship between keratoconus disease and the antioxidant activities of catalase (CAT), reduced glutathione (GSH) and superoxide dismutase (SOD) and the level of the oxidative stress marker malondialdehyde (MDA) in serum. Methods The study included 50 patients diagnosed with keratoconus and 53 healthy age- and sex-matched control subjects. The keratoconus patients were grouped according to the four keratoconus stages based on the modified Krumeich keratoconus classification system. The CAT, GSH and SOD activities and MDA levels in the serum samples collected from the patient and control groups were compared. Results The mean serum CAT, GSH, SOD and MDA levels in the keratoconus group were determined to be 0.075 (0.074–0.078)U/L, 0.002 (0.001–0.006) mmol/ml, 1.56 (1.51–1.62)U/L and 1.69 (1.65–1.99) mmol/L, respectively, and those in the control group were determined to be 0.024 (0.013–0.037)U/L, 0.029 (0.018–0.049) mmol/ml, 4.13 (4.01–4.17) U/L and 0.74 (0.65–0.82) mmol/L. The serum GSH levels and SOD activity were significantly lower in the keratoconus group ( p < 0.001 for both) than in the control group while the CAT activity and MDA levels were significantly higher ( p < 0.001 for both). Conclusion The low serum GSH levels and SOD activity and the high CAT activity and MDA levels observed in this study suggest the presence of oxidative stress and inadequate antioxidant defence mechanisms in keratoconus patients. The studied parameters may offer auxiliary markers for use in the diagnosis and treatment of the keratoconus disease and in its potential therapeutic targets in the future.